RAGE signaling regulates the progression of diabetic complications - Taguchi, Kensei; Fukami, Kei (Frontiers in Pharmacology, 2023)
Diabetes, the ninth leading cause of death globally, is expected to affect 642 million people by 2040. With the advancement of an aging society, the number of patients with diabetes having multiple underlying diseases, such as hypertension, obesity, and chronic inflammation, is increasing. Thus, the concept of diabetic kidney disease (DKD) has been accepted worldwide, and comprehensive treatment of patients with diabetes is required. Receptor for advanced glycation endproducts (RAGE), a multiligand receptor, belonging to the immunoglobulin superfamily is extensively expressed throughout the body. Various types of ligands, including advanced glycation endproducts (AGEs), high mobility group box 1, S100/calgranulins, and nucleic acids, bind to RAGE, and then induces signal transduction to amplify the inflammatory response and promote migration, invasion, and proliferation of cells. Furthermore, the expression level of RAGE is upregulated in patients with diabetes, hypertension, obesity, and chronic inflammation, suggesting that activation of RAGE is a common denominator in the context of DKD. Considering that ligand- and RAGE-targeting compounds have been developed, RAGE and its ligands can be potent therapeutic targets for inhibiting the progression of DKD and its complications. Here, we aimed to review recent literature on various signaling pathways mediated by RAGE in the pathogenesis of diabetic complications. Our findings highlight the possibility of using RAGE- or ligand-targeted therapy for treating DKD and its complications.